Siren City : Sound and Source Music in Classic American Noir. - Miklitsch, Robert (UPCC book collections on Project Muse., 2011)
Siren City engagingly illustrates how sound tracks in 1940s film noir are often just as compelling as the genre's vaunted graphics. Focusing on a wide range of celebrated and less well known films and offering an introductory discussion of film sound, it resonates with the sounds and source music of classic American noir-gunshots and sirens, swing riffs and canaries. Along with the proverbial private eye and femme fatale, these audiovisuals are central to the noir aesthetic and one important reason the genre reverberates with audiences around the world.